The Role of Work Adjustment on Job Involvement Based on Work Value: A Study of Hotel Industry Employees in Ambon, Indonesia - Rehatta, Pieter. N. R. (Open Access Indonesia Journal of Social Sciences, 2023)
Work adjustment refers to the extent to which employees feel that their work is in line with their values and expectations. One important aspect that needs to be understood is the role of work adjustment in shaping job involvement in hotel industry employees in Ambon, Indonesia. Work adjustment includes the extent to which work matches employees' personal values, their expectations of the job, and their suitability for the tasks at hand. Work values are an important factor influencing work adjustment, because individual values play a large role in determining the extent to which someone feels involved and satisfied in their work. This study aimed to determine the role of work adjustment on job involvement based on work values: a study of hotel industry employees in Ambon, Indonesia. This study is research with a quantitative approach and uses primary data obtained from a survey process using a questionnaire, where the survey process was carried out online. The independent variable in this study is job involvement (Y). The dependent variables in this study are work value (X1), work adjustment (X2). The study results show that there is a significant relationship between work value and job involvement, p=0.000. The study results also show that there is a significant relationship between work adjustment and job involvement, p=0.000. The study results also show that there is a significant relationship between work value and work adjustment, p=0.000. In conclusion, work values play a role in work adjustment and work adjustment will play a role in job involvement in hotel industry employees in Ambon, Indonesia.